Succession changes of fermentation parameters, nutrient components and bacterial community of sorghum stalk silage - Zhang, Yawei; Tao, Xinyan; Liu, Qingshan; Zhang, Yue Jiao; Xu, Jiabao; Zhang, Weiyu; Wang, Jing; Zhang, Dandan; Li, Bo; Wang, Lulu; Cheng, Jing; Zhang, Yuan Qing (Frontiers in Microbiology, 2022)
To better understand the ensiling characteristics of sorghum stalk, the dynamic changes of fermentation parameters, nutrient components and bacterial community of sorghum stalk silage were analyzed by intermittently sampling on day 0, 1, 3, 7, 14, 28 and 56 of ensiling duration. The results showed that the high-moisture sorghum stalk was well preserved during ensiling fermentation, with the DM loss of 4.10% and the little difference between the nutrients of sorghum stalk before and after ensiling. The pH value of silage declined to its lowest value of 4.32 by Day 7 of ensiling, and other fermentation parameters kept steady since Day 28 of ensiling. The amplicon sequencing analysis revealed that the alpha diversity parameters of silage bacterial community including Shannon index, observed features, Pielou evenness and Faith PD gradually declined (P < 0.01) with ensiling duration. Principal coordinate analysis revealed that bacterial profiles of raw material would experience a succession becoming a quite different community during ensiling fermentation. Taxonomic classification revealed a total of 10 and 173 bacterial taxa at the phylum and genus level respectively as being detected with relative abundances higher than 0.01% and in at least half samples. LEfSe analysis revealed that 26 bacterial taxa were affected by sampling timepoint (P < 0.05 and LDA score > 4). When focusing on the dynamic trend of silage bacterial taxa, lactic acid bacteria successfully dominated in the bacterial community on Day 1 of ensiling, and the bacterial community almost came to a plateau by Day 28 of ensiling, with Lactobacillus and Leuconostoc as the dominant genera. In a word, the succession of fermentation parameters, nutrient components and bacterial community indicate a successful dominance establishment of LAB and a fast advent of fermentation plateau, suggesting that high-moisture sorghum stalk can be ensiled directly, but the pH of mature silage is a little high.